2014
DOI: 10.1186/1944-3277-9-30
|View full text |Cite
|
Sign up to set email alerts
|

High quality draft genome sequence of the heavy metal resistant bacterium Halomonas zincidurans type strain B6T

Abstract: Halomonas zincidurans strain B6T was isolated from a deep-sea heavy metal rich sediment from the South Atlantic Mid-Ocean Ridge. The strain showed significant resistance to heavy metals, especially to zinc. Here we describe the genome sequence and annotation, as well as the features, of the organism. The genome contains 3,325 protein-coding genes (2,848 with predicted functions), 61 tRNA genes and 6 rRNA genes. H. zincidurans strain B6T encodes 31 genes related to heavy metal resistance. And HGT may play an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…amylovorus [ 32 ]. The decreased relative abundances of Lachnospiraceae, Ruminococcaceae, Erysipelotrichaceae and Ruminococcus might be beneficial to promote growth or alleviate incidence of diarrhea of weaning piglets [ 34 ]. Compared to the control group, Nano-ZnO treatment significantly decreased the Ruminococcus level, while compared with the traditional ZnO treatment, the unclassified bacterial abundance was increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…amylovorus [ 32 ]. The decreased relative abundances of Lachnospiraceae, Ruminococcaceae, Erysipelotrichaceae and Ruminococcus might be beneficial to promote growth or alleviate incidence of diarrhea of weaning piglets [ 34 ]. Compared to the control group, Nano-ZnO treatment significantly decreased the Ruminococcus level, while compared with the traditional ZnO treatment, the unclassified bacterial abundance was increased.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that only 14% of Nano-ZnO could dissolve in gastric fluids [ 13 ] and Nano-ZnO had limited solubility in neutral environment [ 14 ]. In addition, Nano-ZnO particles are unstable in suspension of water, where they aggregate together and continue to increase size beyond the nanoscale [ 34 ]. So the limited impact of Nano-ZnO on cecal microbiota showed in our study might result from the low concentrations of Nano-ZnO and zinc ions dissolved from Nano-ZnO.…”
Section: Discussionmentioning
confidence: 99%
“…2A). All of these bacterial taxa have previously been reported to typically increase rapidly in abundance during oil spills, to degrade hydrocarbons and to tolerate/detoxify heavy metals (Gutierrez et al, 2013;Dubinsky et al, 2013;Kumar et al, 2019;Dell'Anno et al, 2021a,b,c;Huo et al, 2014;Liu et al, 2019;Ramasamy et al, 2020;Ghosh et al, 2022). This suggests that our microbiome enrichment strategy was successful in selectively boosting autochthonous bacterial taxa with promising potential for petroleum hydrocarbon and HM remediation.…”
Section: Characterization Of the Enriched Microbiome And Of The Bacte...mentioning
confidence: 59%
“…The existence of the DnaK gene cluster was widespread in microorganisms who thrive in hydrothermal vents, such as Thiomicrospira ( Tang et al, 2013 ). In addition, H. titanicae SOB56 might be resistant to many metals such as lead, cadmium, zinc, and mercury, similar to H. zincidurans B6 T ( Huo et al, 2014 ). Meanwhile, many reported Halomonas genomes ( Wang and Shao, 2021 ) (including H. titanicae SOB56) in hydrothermal vents carry genes encoding copper resistance proteins, implying the tolerance to such bio-toxic metals in the environment.…”
Section: Discussionmentioning
confidence: 99%